Development of BIDIBO (Biology Digital Book) Based on Digital Flipbook Related to Mangrove Food Processing as a Learning Medium for Students - Wahyuni, Indria; Ratnasari, Dwi; Buana, Nur Gilang; Rifqiawati, Ika (Jurnal Pendidikan Abad Ke-21, 2025)
This study aimed to develop BIDIBO (Biology Digital Book) based on Flipbook Digital as a learning medium, specifically about mangrove food processing. This study also aims to determine the feasibility of the developed product and students' responses to the use of the Biology Digital Book. The research method used is the Research and Development (RD) method. The research was conducted from June to November 2024 at a senior high school in Serang City, Indonesia, and a state university in Banten, Indonesia. The feasibility assessment by subject matter experts on BIDIBO obtained a score of 90%, while the assessment by media experts obtained a score of 95%. Both scores are rated as highly feasible. The student acceptance of the use of BIDIBO was rated at 90.8%, also within the range of high feasibility. Hence, it could be inferred that the Digital Flipbook based on BIDIBO on mangrove food processing is highly feasible for an educational media, especially for the issue on biological diversity.